A low-power X-band free electron laser by prebunching of the electrons - Mohd Fareq, Abdul Malek, Dr.; Lucas, James; Yi, Huang (Wiley Periodicals, Inc., 2011)
Link to publisher's homepage at http://onlinelibrary.wiley.com/